Major Interaction between Warfarin and Na Valproate: A Case Report - Bizhan Kouchaki; Ebrahim Salehifar; Ghasem Janbabai; Ramin Shekarriz; Mahasti Babaeian (Research Center for Rational Use of Drugs (RCRUD), 2015)
Abstract: Warfarin is the most commonly used oral anticoagulant drug in clinical practice with extreme inter and intra-individual variation in pharmacokinetic properties. Na Valproate, a broad spectrum anticonvulsant agent, is best known for its enzyme inhibition properties and also displacement of protein binding sites. Interaction between Warfarin and psychotropic drugs including Valproate are important and perhaps under recognized. In this report, we present a 48 year old female patient with chief complaints of abdominal pain, tea-color urine, blurred vision and headache. She had been suffering from "migraine headache" for 15 years that was relatively well controlled with Na Valproate 200mg twice daily. She was experienced a deep vein thrombosis (DVT) following oral contraceptive. For management of DVT, she was received Warfarin 5mg/day which was increased to 7.5 mg /day after 2 weeks. Three days after this increment of dose, her Prothrombin Time (PT) rose to 35.3 seconds (three times of normal value) and evidences of bleeding including hematuria and hematemesis were observed. Based on the history and laboratory findings, "Warfarin toxicity" was the first impression and she was treated with fresh frozen plasma and vitamin K with a well recovery. This experience emphasizes the clinical significant interaction between Warfarin and Na Valproate, which may take place even with the usual doses of each agent.